2005
DOI: 10.1212/01.wnl.0000178391.96957.d0
|View full text |Cite
|
Sign up to set email alerts
|

Use of serum prolactin in diagnosing epileptic seizures

Abstract: Abstract-Objective:The purpose of this article is to review the use of serum prolactin assay in epileptic seizure diagnosis. Methods: The authors identified relevant studies in multiple databases and reference lists. Studies that met inclusion criteria were summarized and rated for quality of evidence, and the results were analyzed and pooled where appropriate. Results: Most studies used a serum prolactin of at least twice baseline value as abnormal. For the differentiation of epileptic seizures from psychogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(90 citation statements)
references
References 46 publications
(62 reference statements)
2
84
0
3
Order By: Relevance
“…The literature search identified 160 relevant recommendation statements from 19 guidelines [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and 2 consensus papers. [32][33] Review by the co-chairs and facilitator resulted in 20 recommendation statements that were rated highest on importance, validity, strength of evidence, and gaps in care to serve as the evidence base for 12 candidate measures.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 160 relevant recommendation statements from 19 guidelines [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and 2 consensus papers. [32][33] Review by the co-chairs and facilitator resulted in 20 recommendation statements that were rated highest on importance, validity, strength of evidence, and gaps in care to serve as the evidence base for 12 candidate measures.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the age increase in the NES group may be due to conversions. The American Academy of Neurology suggests evaluation of PRL levels in adults and older children to diff erentiate generalized tonic-clonic seizures or complex partial seizures from psychogenic NES at 10-20 min following the attack and interpreting the results in favor of generalized tonic-clonic or partial seizures in case of increased results (14). Yerby et al (13) report that the postictal serum PRL levels used for diff erential diagnosis of ES and NES are not increased in nonepileptic cases in contrast to epileptic cases, and Luef (15) reports that the 15-20 min serum PRL increase may be helpful in diff erentiating between psychogenic and complex partial and generalized tonic-clonic seizures but may not be of help in diff erentiating between epileptic seizure and syncope.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, Oribe et al (16) showed that serum PRL levels were as high as those seen in epilepsies in 21 patients in whom they induced syncopes with tilt test. Leuf (15) showed that PRL was not helpful in diff erentiation of epileptic seizure and syncope; and fi nally Chen et al (14) showed that serum PRL levels were not helpful in diff erentiating epileptic seizure and syncope. Based on the data recorded in our study, we determined that the time of measurement was the only factor aff ecting PRL level, and not any other factor (gender, EEG pathology, antiepileptic drug use, duration of seizures, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…10-20 minutes) after a tonic clonic seizure or CPS and controversially simple partial may be elevated (inconsistent in 60%) [48][49][50][51][52][53].…”
Section: Lab Testsmentioning
confidence: 99%